Real-World Efficacy and Safety of Gemtuzumab Ozogamycin (GO) and 3 + 7 regimen in fit newly diagnosed Acute Myeloid Leukemia (AML) patients. A Retrospective multicenter study of “Rete Ematologica Pugliese” (REP) - M. Dargenio; C. Buquicchio; D. Pastore; L. Aprile; L. Ciuffreda; G. Greco; M. Delia; V. Federico; MP. Fina; D. Seripa; R. Matera; G. Tarantini; et al. (Leukemia Research Reports)
Gemtuzumab Ozogamicin, a monoclonal antibody targeting CD33, linked to calicheamicin, is approved in combination with “3 + 7″ for the treatment of patients with de novo CD33 positive AML. The aim of study was to evaluate the outcome of patients receiving 3 + 7 plus GO as front-line therapy outside clinical trials. Between March 2020 and February 2023, 34 consecutive fit CD33+ AML patients, median age 54.5 years (range, 25–75) were treated. This study confirms the efficacy and toxicity data reported in clinical trials, highlighting the feasibility of GO based chemotherapy also in patients older than 60 years and as a bridge to allo-HSCT.